2019
DOI: 10.1016/j.joca.2018.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum S100A8/S100A9 and knee symptoms, joint structures and cartilage enzymes in patients with knee osteoarthritis

Abstract: Serum levels of S100A8/S100A9 were positively associated with increased knee symptoms, cartilage defects and serum cartilage degradation enzymes in patients with knee OA, suggesting that S100A8/S100A9 may have a role to play in knee OA. Future longitudinal studies are required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Ruan et al showed that levels of serum matrix metalloproteinase (MMP, an enzyme involved in type II collagen degradation) was positively associated with KL grade on Xrays and infrapatellar fat pad signal intensity and medial femur cartilage defects on MRI and was negatively associated with patellar cartilage volume and infrapatellar fat pad volume on MRI 61 . Another study by Ruan et al showed that levels of serum S100A8 and S100A9 (enzymes involved in cartilage degeneration) were positively associated with WOMAC score, cartilage defects on MRI, and serum MMP levels 62 . Joseph et al investigated the association between MRI findings and levels of serum MMP, serum hyaluron (HA, an enzyme involved in osteophyte formation and synovitis), serum cartilage oligomeric matrix protein (COMP, an enzyme involved in cartilage degeneration), and urine carboxy-terminal telopeptides of type II collagen (CTX-II, an enzyme involved in type II collagen degradation).…”
Section: Imaging Findings and Serum And Urine Biomarkers In Knee Oamentioning
confidence: 99%
“…Ruan et al showed that levels of serum matrix metalloproteinase (MMP, an enzyme involved in type II collagen degradation) was positively associated with KL grade on Xrays and infrapatellar fat pad signal intensity and medial femur cartilage defects on MRI and was negatively associated with patellar cartilage volume and infrapatellar fat pad volume on MRI 61 . Another study by Ruan et al showed that levels of serum S100A8 and S100A9 (enzymes involved in cartilage degeneration) were positively associated with WOMAC score, cartilage defects on MRI, and serum MMP levels 62 . Joseph et al investigated the association between MRI findings and levels of serum MMP, serum hyaluron (HA, an enzyme involved in osteophyte formation and synovitis), serum cartilage oligomeric matrix protein (COMP, an enzyme involved in cartilage degeneration), and urine carboxy-terminal telopeptides of type II collagen (CTX-II, an enzyme involved in type II collagen degradation).…”
Section: Imaging Findings and Serum And Urine Biomarkers In Knee Oamentioning
confidence: 99%
“…1) Ampd1 (encodes adenosine monophosphate deaminase 1): Patients with Ampd1 deficiency experience muscle pain (myalgia) or weakness after exercise; 32 2) S100a8 (encodes S100 calciumbinding protein A8): the S100a8 protein is positively associated with increased knee symptoms, cartilage defects in patients with knee osteoarthritis. 33 In addition, KEGG pathway analysis for the DE mRNAs indicates some potential targets, such as inflammatory mediator-regulated transient…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with other recent studies demonstrating a role for MMP-13 in the progression of arthritis. 45 MMPs and their endogenous inhibitors play a critical role in maintaining the dynamic homeostasis and integrity of the extracellular matrix. 6 Previous studies reported that articular chondrocytes from OA knees, rather than normal knees, could express MMP-13.…”
Section: Discussionmentioning
confidence: 99%